Application of Denaturing Gradient Gel Eiectrophoresis(DGGE) Methods on Parent-Offspring Relationship of the Coral Pocillopora damicornis - Dyah Permata Wijayanti; M. Hirose; M. Hidaka (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2008)
DGGE (Denaturing Gradient Gel Eiectrophoresis) is the most powerful methods for mutation detection currently available. In DGGE, DNA fragments of the same length but with different sequences can be separated. The sensitivity of DGGE to slight sequence differences is high since single base changes could be observed. There has been a debate about whether planulae of the coral Pocillopora damicornis are produced sexually or asexually. If produced sexually, planulae are expected to be genetically different from each other and also from their parents. In order to detect possible genetic difference between planulae and their parents, DGGE analysis of ITS2 region of rDNA was used. If there are genetic differences, it is proved that planulae are produced sexually. A total 49 adult colonies and 78 planulae from 11 localities were used for analysis. However, only in 2 families (BiseO1#O2 and Bise02#03YL) showed different DGGE profile, suggesting genetic difference between parent and offspring. The attempt to detect genetic difference in planulae of P. damicornis and their parents using DGGE method was not completely success since DGGE method can not prove clearly the genetic difference between parent and offspring. However, the possibility that DGGE method is applicable for studying coral can be suggested. PCR-DGEE amplification may perform with new STR (short tandem repeat) polymorphic loci of P. damicornis that currently found to answer whether planulae are produced sexually or asexually. Key words : Pocillopora damicornis, planula, DGGE, sexual reproduction, coral